2021
DOI: 10.33594/000000366
|View full text |Cite
|
Sign up to set email alerts
|

scRNA Transcription Profile of Adult Zebrafish Podocytes Using a Novel Reporter Strain

Abstract: BACKGROUND/AIMS: The role of podocytes is well conserved across species from drosophila to teleosts, and mammals. Identifying the molecular markers that actively maintain the integrity of the podocyte will enable a greater understanding of the changes that lead to damage. METHODS: We generated transgenic zebrafish, expressing fluorescent reporters driven by the podocin promoter, for the visualization and isolation of podocytes. We have conducted single cell RNA sequencing (scRNA-seq) on isolated podocytes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Tmsb4x transcripts were also detected in both developing and mature zebrafish podocytes by scRNAseq, suggesting that podocyte expression of Tβ4 is conserved in different species. Interestingly, this study identified a switch in aged podocytes from Tmsb4x to Tmsb1, another member of the beta thymosin family found in zebrafish and other bony fish [34]. TMSB4X transcripts are detected in lysates from adult human glomeruli [29]; however, there is little information about the expression of Tβ4 specifically in podocytes in humans.…”
Section: Tβ4 Expression In Podocytesmentioning
confidence: 83%
“…Tmsb4x transcripts were also detected in both developing and mature zebrafish podocytes by scRNAseq, suggesting that podocyte expression of Tβ4 is conserved in different species. Interestingly, this study identified a switch in aged podocytes from Tmsb4x to Tmsb1, another member of the beta thymosin family found in zebrafish and other bony fish [34]. TMSB4X transcripts are detected in lysates from adult human glomeruli [29]; however, there is little information about the expression of Tβ4 specifically in podocytes in humans.…”
Section: Tβ4 Expression In Podocytesmentioning
confidence: 83%
“…Continued investigations to elucidate the interrelationships and functions of these identified factors are an exciting future area of investigation. Additionally, data from various single cell sequencing approaches [ 158 , 159 , 160 , 161 , 162 ] are expanding our knowledge of the nephron and will be pivotal to advancing knowledge about nephrogenesis, which can be used in future applications such as regenerative medicine [ 163 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of teleost studies have utilized cell isolation and single cell transcriptomics to assist with the identification of brain (17,18), kidney (19), intestine (20) and embryonic (21,22) derived cell populations. Moreover, further work identifying teleost immune cell repertoires in a number of model fish species (23)(24)(25)(26)(27)(28), have established a catalogue of putative immune cell markers that extend beyond those used in mammalian cell identification.…”
Section: Introductionmentioning
confidence: 99%